2018
DOI: 10.1007/s40093-018-0221-y
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of using date branch waste as a peat substitute in container nursery production of lettuce (Lactuca sativa L.)

Abstract: Purpose Peat-based substrates constitute the preferred media in conventional and organic nursery production. Nevertheless, in recent years, there has been a growing interest in environmental impacts associated with peat extraction that has increased with the demand of these non-renewable substrates. The re-use of organic wastes as substrate seems to be good solution to substitute commercial peat. This study evaluates date-palm peat (wastes of date-palm branches base locally known as "Kornef") as an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…Previous funding comparing date palm waste to other growing substrates in soilless culture concluded that date palm waste is an appropriate medium for soilless culture with suitable physical and chemical properties, availability, and low cost [21]. Therefore, it might be a novel substrate that displaces other media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous funding comparing date palm waste to other growing substrates in soilless culture concluded that date palm waste is an appropriate medium for soilless culture with suitable physical and chemical properties, availability, and low cost [21]. Therefore, it might be a novel substrate that displaces other media.…”
Section: Discussionmentioning
confidence: 99%
“…Date-palm substrate presents a low amount of bulk density and a high amount of porosity related [19] that allows the plant root to penetrate in substrate easily, and it could use more volume and space of media [20,21]. It has a higher water-holding capability than CF and can absorb water 8.5 times its dry weight [13].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, date cultivation is an important sector in North Africa and the Gulf region. Worldwide, an estimated amount of over 3,675,000 tons of residue is discarded annually, leading to environmental problems [ 14 ]. Therefore, this experiment compares the growth, physiological parameters, and production of tomatoes grown on date-palm waste and local soil to those grown on a commercial soilless substrate: coco-peat.…”
Section: Discussionmentioning
confidence: 99%
“…There are around 105 million palm trees worldwide and an approximate 3,675,000 tons of waste are dumped annually [ 14 ], causing environmental hazards [ 15 , 16 ]. The most frequent types of date-palm waste are fronds, branches, stem bark, and leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The waste of date palm includes its branches, stem barks, fronds, and leaves. While it has a higher value of water holding capacity than coco peat substrate, it is most commonly produced by pruning date palm trees each year [ 20 ]. According to previous reports, the performance of palm-date wastes as substrate was similar to, or even better than, peat, perlite, and coco peat substrates [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%